Plant neighbour-modulated susceptibility to pathogens in intraspecific mixtures. (14th June 2021) - Pélissier, Rémi; Buendia, Luis; Brousse, Andy; Temple, Coline; Ballini, Elsa; Fort, Florian; Violle, Cyrille; Morel, Jean-Benoit
Abstract : Susceptibility to fungal pathogens and plant immunity in rice and wheat can be modulated by the presence of intraspecific neighbours and does not require the neighbours to be infected. Abstract: As part of a trend towards diversifying cultivated areas, varietal mixtures are subject to renewed interest as a means to manage diseases. Besides the epidemiological effects of varietal mixtures on pathogen propagation, little is known about the effect of intraspecific plant–plant interactions and their impact on responses to disease. In this study, genotypes of rice ( Oryza sativa ) or durum wheat ( Triticum turgidum ) were grown with different conspecific neighbours and manually inoculated under conditions preventing pathogen propagation. Disease susceptibility was measured together with the expression of basal immunity genes as part of the response to intra-specific neighbours. The results showed that in many cases for both rice and wheat susceptibility to pathogens and immunity was modified by the presence of intraspecific neighbours. This phenomenon, which we term 'neighbour-modulated susceptibility' (NMS), could be caused by the production of below-ground signals and does not require the neighbours to be infected. Our results suggest that the mechanisms responsible for reducing disease in varietal mixtures in the field need to be re-examined.